PERSENTASE LIMBAH PADA INDUSTRI SAWMILL PT. BERAU KARYA INDAH DI KABUPATEN TELUK BINTUNI - YAYA; RUSDI ANGRIANTO; YOHANES Y. RAHAWARIN (Fakultas Kehutanan UNIPA, 2020)
The goal of this study was to understand the types of wood waste and its percentage emanating from sawmill industry. The study situated in sawmill industry of PT. Berau Karya Indah, district of Teluk Bintuni. Data were performed in tabulation and exhibited in tables and images. The results indicated that wood waste obtained from wood processing was about 49.73% that consisted of wood sawdust around 20.69%, slash waste was about 29.03%. In detail, presentation of each detailed unit machine was elaborated such as breakdown saw produced about 4.20 %, ponny produced wood sawdust approximately 11.50 %, resaw indicated sawdust roughly 27 %, while from crosscut, the process produced sawdust approximately 7.02%. Another reuse wood waste was noticed for packing from the slash waste, but the overall wood waste has not been used proportionally due to lack of community engagement.